Desain dan Implementasi Data Warehouse Penjualan pada Chinook Sample Database - Putra, Gusti Ngurah Deva Wirandana; Pramartha, Cokorda Rai Adi (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 2 (2023): JELIKU Volume 12 No 2, November 2023, 2023)
The company's decision making is very important for analysis. With the data warehouse can support the process of analysis, design, and business decision making of the company. The company stores operational data that is useful in the business analysis process into a data warehouse. This study will develop the design and implementation of a data warehouse using the Chinook Sample Database as the source. Used Nine-Step Design Methodology to design the data warehouse and through the ETL (Extract, Transformation, Loading) process. The results form a Dashboard that is visualized with Tableau according to a sales fact chart that contains information used to assist the company's business analysis and decisions.